Development and validation of an endoplasmic reticulum stress long non-coding RNA signature for the prognosis and immune landscape prediction of patients with lung adenocarcinoma - Zeng, Jie; Wu, Zhenyu; Luo, Meijuan; Xu, Xie; Bai, Wenjie; Xie, Guijing; Chen, Quhai; Liang, Dengfeng; Xu, Zixun; Chen, Mindong; Xie, Jianjiang (Frontiers in Genetics, 2023)
Background: Lung adenocarcinoma (LUAD), the most common histotype of lung cancer, may have variable prognosis due to molecular variations. This work investigated long non-coding RNA (lncRNA) related to endoplasmic reticulum stress (ERS) to predict the prognosis and immune landscape for LUAD patients. Methods: RNA data and clinical data from 497 LUAD patients were collected in the Cancer Genome Atlas database. Pearson correlation analysis, univariate Cox regression, least absolute shrinkage and selection operator regression analyses, as well as the Kaplan-Meier method, were used to screen for ERS-related lncRNAs associated with prognosis. The risk score model was developed using multivariate Cox analysis to separate patients into high- and low-risk groups and a nomogram was constructed and evaluated. Finally, we explore the potential functions and compared the immune landscapes of two groups. Quantitative real-time PCR was used to verify the expression of these lncRNAs. Results: Five ERS-related lncRNAs were shown to be strongly linked to patient prognosis. A risk score model was built by using these lncRNAs to categorize patients based on their median risk scores. For LUAD patients, the model was found to be an independent prognostic predictor (p < 0.001). The signature and clinical variables were then used to construct a nomogram. With 3-year and 5-year OS’ AUC of 0.725 and 0.740, respectively, the nomogram's prediction performance is excellent. The 5-lncRNA signature was associated with DNA replication, epithelial-mesenchymal transition, and the pathway of cell cycle, P53 signaling. Between the two risk groups, immune responses, immune cells, and immunological checkpoints were found to be considerably different. Conclusion: Overall, our findings indicate that the 5 ERS-related lncRNA signature was an excellent prognostic indicator and helped to predict the immunotherapy response for patients with LUAD.